"We Know Nothing About Yemen!" Ottoman Imperial Governance in Southwest Arabia and the Politics of Knowledge Production, 1871–1914. Issue 1 (2nd January 2018) - Kuehn, Thomas
Abstract: This article analyzes changing concepts and practices of knowledge production and governance in the Ottoman Province of Yemen from the re-conquest of the Yemeni highlands in 1871–3 to the beginning of the First World War. It argues that, while Ottoman bureaucrats embraced modern governmentality by emphasizing the connection between local knowledge and effective governmental control, the production of knowledge about the political, social, cultural, and economic realities of southwest Arabia during this period cannot be reduced to acts of writing and the creation of government archives. While historians of the late Ottoman Empire have often suggested that knowledge production –– like other elements of imperial governance during the period under study –– became increasingly systematic and informed by bureaucratic rationality, I argue that in fact personal relations and oral communications remained the hallmarks of Ottoman knowledge production in Yemen until the early twentieth century. This began to change when the near collapse of Ottoman rule in Yemen in 1905, the end of the Hamidian regime in 1908–09, and new notions of professionalism prompted officials to view existing practices of knowledge production and transmission as partly responsible for the government's failure to control this province. Now, they increasingly associated authoritative knowledge with published, scholarly accounts, while considering unrecorded knowledge unreliable.